Cryptosporidiosis of the biliary tract mimicking pancreatic cancer in an AIDS patient - Do Rosário de Souza, Lenice [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Morceli, José [UNESP]; Kemp, Raphael [UNESP]; Mendes, Rinaldo Poncio [UNESP] (FapUNIFESP (SciELO), 2004)
Diarrhea caused by Cryptosporidium sp is frequent in patients with AIDS, but involvement of other organs of the digestive tract is uncommon. We report a case of Cryptosporidium-associated obstruction of the biliary tract mimicking cancer of the head of the pancreas in a 43-year-old woman with AIDS.
Keywords: AIDS; Biliary tract; Cryptosporidiosis; Pancreatitis; antiretrovirus agent; clarithromycin; fluconazole; indinavir; lamivudine; stavudine; acquired immune deficiency syndrome; adult; bile duct obstruction; case report; clinical feature; cryptosporidiosis; diarrhea; differential diagnosis; disease course; female; hepatobiliary system; human; pancreas cancer; Adult; AIDS-Related Opportunistic Infections; Animals; Cholestasis; Fatal Outcome; Female; Humans; Pancreatic Neoplasms; Cryptosporidium; Pomacanthus maculosus